A history of the Renaissance - Schlessinger, Andrew; V. Dennett, Ashleigh; Schlessinger Media; Tremendous Entertainment (Wynnewood, PA : Schlessinger Media, 2004)
This video investigates the driving forces behind this brilliant period of artistic and scientific achievement. discover how humanists like Petrarch pioneered the rediscovery of ancient Greek and Roman culture and ideas, sparking and explosion of creativity and innovation
Teacher's guide and other resources on this topic are available online
Grades 5-9
Executive producer, Andrew Schlessinger ; produced and directed by, Ashleigh V. Dennett ; writer, Dave Rodrich ; edited by, Jay Gallentine, Angela Heins
Keywords: Renaissance; Humanism; Civilization, Modern